Perioperative Use of Gabapentinoids for the Management of Postoperative Acute Pain: A Systematic Review and Meta-analysis. (August 2020) - Verret, Michael; Lauzier, François; Zarychanski, Ryan; Perron, Caroline; Savard, Xavier; Pinard, Anne-Marie; Leblanc, Guillaume; Cossi, Marie-Joëlle; Neveu, Xavier; Turgeon, Alexis F.; McAuley, Al; Flexman, Alana; et al.
Abstract : Background: Widely used for acute pain management, the clinical benefit from perioperative use of gabapentinoids is uncertain. The aim of this systematic review was to assess the analgesic effect and adverse events with the perioperative use of gabapentinoids in adult patients. Methods: Randomized controlled trials studying the use of gabapentinoids in adult patients undergoing surgery were included. The primary outcome was the intensity of postoperative acute pain. Secondary outcomes included the intensity of postoperative subacute pain, incidence of postoperative chronic pain, cumulative opioid use, persistent opioid use, lengths of stay, and adverse events. The clinical significance of the summary estimates was assessed based on established thresholds for minimally important differences. Results: In total, 281 trials (N = 24, 682 participants) were included in this meta-analysis. Compared with controls, gabapentinoids were associated with a lower postoperative pain intensity (100-point scale) at 6 h (mean difference, −10; 95% CI, −12 to −9), 12 h (mean difference, −9; 95% CI, −10 to −7), 24 h (mean difference, −7; 95% CI, −8 to −6), and 48 h (mean difference, −3; 95% CI, −5 to −1). This effect was not clinically significant ranging below the minimally important difference (10 points out of 100) for each time point. These results were consistent regardless of the type of drug (gabapentin or pregabalin). No effect was observed on pain intensity at 72 h, subacute and chronic pain. The use of gabapentinoids was associated with a lower risk of postoperative nausea and vomiting but with more dizziness and visual disturbance. Conclusions: No clinically significant analgesic effect for the perioperative use of gabapentinoids was observed. There was also no effect on the prevention of postoperative chronic pain and a greater risk of adverse events. These results do not support the routine use of pregabalin or gabapentin for the management of postoperative pain in adult patients. Abstract : In a meta-analysis of 281 randomized controlled trials comparing gabapentinoids with controls, no clinically meaningful difference in acute, subacute, or chronic pain was observed. Although the risk of postoperative nausea and vomiting was slightly lower, adverse events of dizziness and visual disturbance were greater with gabapentinoid use.Supplemental Digital Content is available in the text.